Shear Strength of the Selected Types of Pellets (Agricultural Engineering, 2016)
The usefulness of raw material obtained from oak leaves, waste from paper mass and fragments of Miscanthus was verified with regard to pellet production. A batch of pellets produced therefrom was subjected to technological shear tests with the use of prototype equipment. Also pellets produced by well-known Polish producers were tested. The suggested method of technological shear enables obtaining credible results through standardization of tests conditions. Statistical processing of results proved that there are significant differences in the values of shear strength and unit shear work obtained for both group of pellets. An experimental batch of pellets has a lower density and thus lower shear strength which limits the scope of industrial application. The research which was carried out proved that there is a strong correlation between mechanical strength and density.